"Meu destino tá traçado. vou ser marginal": a construção de sentidos-e-significados sobre a violência em escola pública - Santos, Miriam Márcia de Souza (2010)
This research aims at investigate the comprehension of sense-and-meanings of certain experiences of students at a public school located in São Paulo, whose daily life is marked by violence. More specifically, we study how the experiences in contexts of violence permeate the daily life of students, becoming a constituent of aggressive attitudes and behaviors of students with one another and for staff schoolchildren. We sought to characterize the school environment as a space for interaction, in which symbolic violence and physical assault intersect. Participating in this research 7 teachers, teacher pedagogical coordinator and researcher-trainer plus 6 students from 6th and 7th grade on. Thus, the investigation opened up possibilities for thinking about school and family as a place of conflict mediation and the coexistence of social. Centered and cultural diversity in a critique of methodological search interpretive (Moita Lopes, 1994), this study further issues relating to education and affection, anchored in the Theory Socio-Cultural History, and discuss the following key theoretical assumptions: the mediation in the teaching- learning and development (Vygotsky, 1934/2003; Newman and Holzman, 2002, and others), senses and meanings (Vygotsky, 1934/2001; González Rey, 2000; Aguiar, 2000; Bakhtin; 1929-30/1992; and others) and the emotions and feelings (Vygotsky, 1930/2004; Aguiar, 2006; González Rey, 2005, and others) to see what the senses-and-meanings, participants were studied by the topical (Koch, 1998 ). The data reveal that there is strong evidence that aggressive behavior at school, in most cases is linked to students' lack of affection